TINJAUAN YURIDIS TENTANG PEMILIKAN RUMAH ORANG ASING YANG BERKEDUDUKAN DI INDONESIA - Dhona Anggun Sutrisna; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
Investment is the source of funds management activities at the present time with the aim of obtaining maximum profits in the future. In order to improve the country’s economic growth in Indonesia, the government took measures to attract capital from abroad by way of foreign investment. The method used in this research is normative with descriptive analytical research specification, whereas the data analysis method used is qualitative analysis. Based on the results of research and discussion can be concluded that the arrangements regarding the ownership of residential home for foregners domiciled in Indonesia is the Law of the Republic of Indonesia Number 5 of 1960 on the Basic Regulation of Agrarian Principles ( BAL ) and the execution of the Indonesian Government Regulation Number 103 of 2015 on Housing Residential Dwelling Or By Stranger that domiciled in Indonesia. Procedures for settling disputes regarding ownership of residential home for foreigners domiciled in Indonesia resolved through litigation and non-litigation.Keywords : Investment, Foreigners, Home Shelter.